(3GbJUGOjGJ GdGSJKeGQ h GdJehjd h GdJMdjd GdeGdj (B/s - (3YHO GdQMje, eMeO GHQGgjes ((3GdGScfOQjI(B: s (3eDSSI THGH GdLGeYI(B, s, 2008)
(3CgejI GdGOGQI GdeGdjI GJNGP bQGQGJ GdJehjd (B-(3GdJehjd bUjQ GdGLd (B-(3GdGSJKeGQ aj GdGhQGb GdeGdjI (B-(3fehPL JSYjQ GdGUhd GdQCSeGdjI h Jbjje GdGSJKeGQ aj GdGhQGb GdeGdjI (B-(3Jbjje GdbQGQGJ GdGSJKeGQjI (B- (3GdJMdjd GdeGdj h JMdjd QCS GdeGd GdYGed , GdJfHD HGdaTd GdeGdj , Jbjje h JSYjQ GdCUhd , bjGS bjeI GdefTCI , GdbjeI GdeVGaI GdGbJUGOjI , GdEjLGQ h GdTQGA GdJCLjQj h CNjQG GdJNWjW GdeGdj(B.s
((3GbJfGAGJ (B2014 3(3f(B)s
Keywords: (3GdGOGQI GdeGdjIs; (3GdGSJKeGQs; (3GdJMdjd GdeGdjs; (3GdJehjds